2008
DOI: 10.1080/09540120701426557
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for distress in the adolescent children of HIV-positive and HIV-negative drug-abusing fathers

Abstract: In contrast to previous research on parental drug abuse, the present study examined comorbid drug addiction and HIV infection in the father as related to his adolescent child's psychological distress. Individual structured interviews were administered to 505 HIV-positive and HIV-negative drugabusing fathers and one of their children, aged 12-20. Structural equation modeling tested an hypothesized model linking paternal latent variables, ecological factors, and adolescent substance use to adolescent distress. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…A study of the adolescent children of drug-using, HIV positive fathers (n = 505) found direct associations between paternal distress and adolescent distress [ 69 ]. In addition, they described several indirect pathways, such as the link between paternal distress and impaired paternal teaching of coping skills, adolescent substance use, and ultimately, adolescent distress.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the adolescent children of drug-using, HIV positive fathers (n = 505) found direct associations between paternal distress and adolescent distress [ 69 ]. In addition, they described several indirect pathways, such as the link between paternal distress and impaired paternal teaching of coping skills, adolescent substance use, and ultimately, adolescent distress.…”
Section: Resultsmentioning
confidence: 99%
“…2 Fathers who experience a mental illness may have impairments in parenting practices 36 that place their children at increased risk for mental illness and poor functioning. 719 Therefore, more research is needed on fathers’ mental health, particularly among racial and ethnic populations who have known risk factors for mental disorders.…”
mentioning
confidence: 99%
“…Γενικότερα, φάνηκε ότι η διαθεσιμότητα ουσιών, όπως σημειώνει και ο Roberts (1999), η ανοχή της «ήπιας» χρήσης και της παραβατικής συμπεριφοράς, χαρακτηριστικό του οικογενειακού τρόπου ζωής, σε συνδυασμό με τα ελλιπή όρια και τις σχέσεις ευνόησαν την συναναστροφή με παραβατικούς εφήβους και την έναρξη της χρήσης. Χαρακτηριστικά στη βιβλιογραφία τονίζεται η μεταβίβαση αρνητικών γονεϊκών προτύπων, όπως η διαγενεακή μεταβίβαση της παραβατικότητας ως γονεϊκής νόρμας, σε σχέση με την έναρξη χρήσης στα παιδιά εξαρτημένων γονέων (Castro et al, 2006;Moss et al, 2003) (Brook et al, 2006a;Stanger et al, 2002) με δεδομένο την υφιστάμενη περιορισμένη διδαχή διαχείρισης δεξιοτήτων στα παιδιά εκ μέρους των γονέων (Brook et al, 2008). Συγκεκριμένα, ο Bays (1990) (Stromwall et al, 2008), με προεξάρχουσες διαταραχές διάθεσης (Beckwith et al, 1999;Jones et al, 2004;Pajulo et al, 2001), προσωπικότητας και ψυχώσεις (Beckwith et al, 1999;Espinosa et al, 2001;Howard et al, 1995).…”
Section: βίωμα πολλαπλών απωλειώνunclassified